59 Correlates of digital dating violence among high-risk emerging adults. (19th September 2017) - Hong, Jhuree; Stein, Sara F; Zbizek-Nulph, Lisa; Ramirez, Jessica; Cunningham, Rebecca M; Walton, Maureen A; Chermack, Stephen
Abstract : Purpose: Digital dating violence (DDV) is an issue of concern with increases in technology use among emerging adults (EA). Despite this surge, predictors of DDV perpetration remain understudied, particularly among non-college EAs. This study examines the relationship between DDV perpetration, trait mindfulness, dating partner residence, receipt of public assistance, and demographic characteristics among at-risk EAs. The evaluation of correlates of DDV perpetration will inform the development of effective treatment interventions. Methods: EAs (n=775) ages 18–25 years treated in the emergency department (ED) for any reason completed a self-administered computerised survey. Ordinary least squares linear regression with a Poisson distribution was conducted to examine associations between DDV perpetration and trait mindfulness, dating partner residence, receipt of public assistance, and demographic characteristics. Results: Thirty-seven percent of the sample was comprised of women, 43% received public assistance, and 25% lived with a dating partner. The majority of the sample identified as Black (61%), while the remaining as Caucasian (39%). Analyses indicated that higher levels of trait mindfulness were associated with lower levels of DDV perpetration (Î²=−0.06, p<0.001). Results further revealed that partner residence (Î²=0.40, p<0.05) and receiving public assistance (Î²=0.44, p<0.01) significantly predicted higher levels of DDV perpetration. Age, gender, and racial group were not significantly related. Conclusions: These findings indicate that lower levels of trait mindfulness, living with a partner and receiving public assistance (likely indicative of economic stressors) were associated with more DDV perpetration. Interventions aimed at reducing DDV perpetration should give special attention to these characteristics. Contributions: This work is part of a growing body of research aimed at developing evidenced-based interventions for DDV perpetration. The identification of correlates of DDV perpetration will contribute to the development of more effective interventions to mitigate this type of aggression.